Heuristics in novice investors' behaviours as an associated network - Maciejasz-Świątkiewicz, Marta (Heurystyki w zachowaniach początkujących inwestorów jako sieć naczyń powiązanych, 2012)
The article presents heuristics in the decision-making process of the beginning investors. The number of effects and correlations between them was measured according to investors self-descriptions (made during the game Cashflow 101). It seems that there are some effects that coexist and this can be explained by psychological theories
Nauki o Finansach = Financial Sciences, 2012, Nr 1 (10), s. 155-165
Keywords: bechavioural finance; heuristics; financial behaviours; finanse behawioralne; heurystyka; zachowania finansowe